2009
DOI: 10.1002/mus.21519
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells as a source of insulin‐like growth factor‐1 for extraocular muscles

Abstract: Precise force regulation is fundamentally important for extraocular muscle (EOM) function. Insulin-like growth factor-1 (IGF-1) plays a major role in EOM force regulation, but the source of endogenous IGF-1 is unclear. Multiple IGF-1 sources may supply EOMs, including: the EOM itself; the systemic circulation; innervating motoneurons; and Schwann cells within nerves. IGF-1 expression was measured in chicken during oculomotor system maturation by using real-time polymerase chain reaction (PCR). Accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Indeed, some growth factors, trophic factors, and cytokines can be transported anterogradely in nerves, including motor nerves [65, 67]. Our recent study on IGF1 showed that this growth factor is prominently expressed by Schwann cells in oculomotor nerves, and IGF1 protein can be transported from the nerve to EOMs [21]. Nevertheless, our current study shows that the EOMs per se express much more IGF1, CT1, and GDNF than limb skeletal muscles.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Indeed, some growth factors, trophic factors, and cytokines can be transported anterogradely in nerves, including motor nerves [65, 67]. Our recent study on IGF1 showed that this growth factor is prominently expressed by Schwann cells in oculomotor nerves, and IGF1 protein can be transported from the nerve to EOMs [21]. Nevertheless, our current study shows that the EOMs per se express much more IGF1, CT1, and GDNF than limb skeletal muscles.…”
Section: Discussionmentioning
confidence: 68%
“…GoTaq green master mix (Promega, Madison, WI, USA) was used for qualitative PCR. “RT minus” control was used to detect possible genomic DNA contamination, as described previously [21]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experiments, geNorm ranked GAPDH as one of the two most stably expressed genes (GAPDH and EF1A2). We chose GAPDH as the reference gene for two reasons: because of its stable expression and its use for quantifying skeletal muscle IGF-1 expression in previous studies, thus making our data comparable with those generated in other labs (Cheema et al, 2005; Fischer et al, 2005; Heinemeier et al, 2007; Feng and von Bartheld, 2010; Li et al, 2011). The amplification efficiencies of all primers were within 90%–110%.…”
Section: Resultsmentioning
confidence: 99%